E-Cigarette and Cannabis Use Patterns, Depression, and Suicide Behaviors Among US Youth: Analysis of 2019 Youth Risk Behavior Survey Data - Jacobs, Wura; Orozco, Georgina; Villanueva, Guadalupe; Merianos, Ashley L (American journal of health promotion, 2023)
Purpose To examine the associations of current electronic cigarette and cannabis use patterns with depression symptoms and suicidal ideation and behavior overall and stratified by sex among U.S. high school students. Design Quantitative, cross-sectional study. Setting The 2019 National Youth Risk Behavior Survey. Subjects 12,401 high school students in 9th−12th grade. Measures Dependent variables were depression symptoms, suicidal ideation, suicide plan, suicide attempt, and suicide attempt-related injury. Independent variables were past 30 day e-cigarette and cannabis use patterns. Covariates included demographics, grade level, and other tobacco product use. Analysis Multivariable logistic regression models. Results Approximately 15.7% of students were exclusive e-cigarette users, 4.5% were exclusive cannabis users, and 16.4% were concurrent e-cigarette and cannabis users. Exclusive e-cigarette and cannabis users, and concurrent users were at increased odds (P < .05) of having depression symptoms, seriously considered attempting suicide, planning suicide, suicide attempt, and having suicide attempt-related injury compared to non-users. Female users, especially concurrent users, had higher odds of reporting depression symptoms (P < .01) and all suicidal ideation and behavior outcomes (P < .01) than female non-users, but results varied for male students. Conclusion E-cigarette and cannabis use patterns significantly predicted depression symptomatology and suicidal ideation and behavior, with female students having higher odds. Results suggest the need for tailored interventions to address mental health and suicidality among U.S. adolescents, and especially female students.